Negative electrode and lithium secondary battery comprising the same
By combining carbon-based and silicon-based materials in the negative electrode active material of lithium secondary batteries and controlling the particle shape and particle size ratio, the problems of fast charging performance and charge/discharge efficiency were solved, thereby improving battery capacity and lifespan.
Patent Information
- Application Number
- CN202580021992.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-10-24
- Filing Date
- 2025-10-27
- Publication Date
- 2026-11-03
AI Technical Summary
Existing lithium secondary batteries have shortcomings in terms of fast charging performance and charge/discharge efficiency, especially due to the degradation of battery performance caused by particle breakage of graphite-based active materials and electrolyte side reactions.
The negative electrode active material is made up of carbon-based and silicon-based active materials. By controlling the sphericity of the primary particles and the ratio of the average particle size of the silicon-based active material to the average particle size of the artificial graphite particles in the secondary particle form within a specific range, side reactions and material breakage are suppressed, ensuring the lithium-ion diffusion path.
It improves the battery capacity, cycle life, and fast charging performance of lithium secondary batteries, reduces battery internal resistance, and prevents battery performance degradation.
Smart Images

Figure SMS_1 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] This invention relates to a negative electrode and a lithium secondary battery containing the negative electrode. Background Technology
[0002] With increasing concern about environmental issues, extensive research has been conducted on electric vehicles (EVs) and hybrid electric vehicles (HEVs), which can replace vehicles using fossil fuels such as gasoline and diesel vehicles, which are major contributors to air pollution. The main research focuses on lithium-ion batteries with high energy density, high discharge voltage, and high output stability, and their application as power sources for these EVs and HEVs.
[0003] Typically, a lithium secondary battery is constructed by comprising a positive electrode, a negative electrode, a separator, and an electrolyte. The positive or negative electrode is prepared by mixing the positive or negative active material with a binder and dispersing the mixture in a solvent to prepare a slurry, and by coating the slurry onto the surface of an electrode current collector and drying it to form an electrode active material layer.
[0004] In this context, carbon-based active materials that can reversibly insert and extract lithium ions while maintaining their structure and electrical properties can be used as the negative electrode active material. Various types of carbon-based materials (such as artificial graphite, natural graphite, and hard carbon) have been used as carbon-based active materials, and among them, graphite-based active materials, which ensure the lifespan characteristics of lithium-ion secondary batteries due to their excellent reversibility, are the most widely used. Because graphite-based active materials have a low discharge voltage of -0.2 V relative to lithium, batteries using graphite-based active materials can exhibit a high discharge voltage of 3.6 V, thus offering many advantages in terms of energy density for lithium-ion batteries.
[0005] On the other hand, with the development of electric vehicles and mobile electronic devices, in order to meet consumers' demands for convenience, efficiency and economy, attempts have been made to improve fast charging performance, and efforts have been made to increase the amount of carbon coating on graphite-based active materials and form secondary particles of artificial graphite, but problems such as reduced charging and discharging efficiency exist.
[0006] Therefore, there is an urgent need to develop a negative electrode that can simultaneously improve fast charging performance and charge / discharge efficiency. Summary of the Invention
[0007] Technical issues
[0008] The purpose of this invention is to provide a negative electrode using a negative electrode active material comprising a carbon-based active material and a silicon-based active material. The carbon-based active material comprises artificial graphite particles in the form of secondary particles formed by the aggregation of multiple primary particles. By designing the sphericity of the primary particles and the ratio of the average particle size of the silicon-based active material to the average particle size of the artificial graphite particles in the form of secondary particles to have values within a specific range, side reactions with the electrolyte and side reactions of the material itself are suppressed, thereby preventing a decrease in discharge capacity, reducing battery internal resistance, and having improved cycle life and fast charging performance.
[0009] Another object of the present invention is to provide a lithium secondary battery comprising the above-described negative electrode.
[0010] Technical solution
[0011] The present invention provides a negative electrode comprising a current collector; and a negative electrode active material layer disposed on at least one surface of the current collector, wherein the negative electrode active material layer comprises a carbon-based active material and a silicon-based active material, the carbon-based active material comprising artificial graphite particles in the form of secondary particles formed by the aggregation of a plurality of primary particles, the sphericity of the primary particles being in the range of 0.60 to 0.78, and the average particle size (D) of the silicon-based active material being... 50 The average particle size (D) of the artificial graphite particles in the secondary particle form 50 The ratio is in the range of 0.4 to 1.
[0012] Furthermore, the present invention provides a lithium secondary battery comprising the aforementioned negative electrode.
[0013] Beneficial effects
[0014] The negative electrode according to the present invention employs a negative electrode active material comprising a carbon-based active material and a silicon-based active material. The carbon-based active material comprises artificial graphite in the form of secondary particles formed by the aggregation of a plurality of primary particles. In this case, the sphericity of the primary particles constituting the artificial graphite particles in the form of secondary particles is controlled to meet a specific range. Specifically, since the shape of the primary particles is adjusted to be close to spherical, side reactions with the electrolyte caused by particle breakage and increased specific surface area after the calendering process during the preparation of the negative electrode can be prevented, and the diffusion path of lithium ions can be ensured to form a stable film.
[0015] Furthermore, because lithium ions can be embedded within the silicon-based active material particles when the ratio of the average particle size of the silicon-based active material to the average particle size of the artificial graphite particles in secondary particle form is controlled within a specific range, the degradation rate of the silicon-based active material can be reduced, thus suppressing particle breakage. Additionally, the problem of reduced impregnation capacity of the negative electrode due to byproducts clogging the pores of the negative electrode as the solid electrolyte interphase (SEI) film formed on the surface of the silicon-based active material is destroyed can be minimized. As a result, degradation of battery life performance, capacity performance, and fast-charging performance can be prevented.
[0016] Therefore, the negative electrode according to the present invention can simultaneously achieve the effect of increasing battery capacity due to the use of silicon-based active materials, and the effect of reducing battery resistance and improving fast charging performance by controlling the ratio of the sphericity of primary particles and the average particle size of silicon-based active materials to the average particle size of artificial graphite particles in the form of secondary particles. Detailed Implementation
[0017] It will be understood that the words or terms used in the specification and claims should not be interpreted as having the meaning defined in a common dictionary, and it will be further understood that, based on the principle that the inventors may appropriately define the meaning of words or terms to best interpret the invention, the words or terms should be interpreted as having a meaning consistent with their meaning in the context of the relevant field and in the technical idea of the invention.
[0018] The terminology used herein is for the purpose of describing particular exemplary embodiments only and is not intended to limit the invention. In the specification, singular terms may include plural forms unless otherwise stated.
[0019] It will also be understood that the terms “comprising,” “including,” or “having” as used in this specification specify the presence of the stated features, figures, steps, elements, or combinations thereof, but do not exclude the presence or addition of one or more other features, figures, steps, elements, or combinations thereof.
[0020] The average particle size (D) in this specification 50 The average particle size (D) can be defined as the particle size that constitutes 50% of the cumulative volume in the particle size distribution curve. For example, it can be measured using laser diffraction. 50 Laser diffraction methods can typically measure particle sizes ranging from submicron to millimeters, and can yield highly repeatable and high-resolution results.
[0021] In this specification, the term "primary particle" means a single particle, that is, one particle, and the term "secondary particle" means an aggregate of multiple primary particles that are brought together through an intentional assembly or combination process.
[0022] The present invention will be described in detail below.
[0023] negative electrode
[0024] This invention relates to negative electrodes, and more specifically, to negative electrode active materials for lithium secondary batteries.
[0025] Specifically, the negative electrode according to the present invention is characterized in that it comprises a current collector; and a negative electrode active material layer disposed on at least one surface of the current collector, wherein the negative electrode active material layer comprises a carbon-based active material and a silicon-based active material, the carbon-based active material comprising artificial graphite particles in the form of secondary particles formed by the aggregation of a plurality of primary particles, the primary particles having a sphericity of 0.60 to 0.78, and the silicon-based active material having an average particle size (D) 50 The average particle size (D) of the artificial graphite particles in the secondary particle form 50 The ratio is in the range of 0.4 to 1.
[0026] Current collectors commonly used in the art can be used without limitation. For example, the current collector is not particularly limited, as long as it has high conductivity and does not cause chemical changes in the lithium secondary battery. For example, the negative electrode current collector may contain at least one selected from copper, stainless steel, aluminum, nickel, titanium, calcined carbon, and aluminum-cadmium alloys, preferably copper.
[0027] The current collector may have fine surface irregularities to improve the bonding strength with the negative electrode active material, and the current collector may be used in various shapes, such as membrane, sheet, foil, mesh, porous body, foam, non-woven fabric, etc.
[0028] The negative electrode current collector can typically have a thickness of 3μm to 500μm.
[0029] The negative electrode active material layer is disposed on at least one surface of the negative electrode current collector. Specifically, the negative electrode active material layer may be disposed on one or both surfaces of the negative electrode current collector.
[0030] The negative electrode active material layer contains a negative electrode active material.
[0031] The negative electrode active material includes carbon-based active materials and silicon-based active materials.
[0032] The carbon-based active material and the silicon-based active material can each be in the form of particles.
[0033] The carbon-based active material comprises artificial graphite particles in the form of secondary particles formed by the aggregation of multiple primary particles.
[0034] Silicon-based active materials offer advantages such as higher capacity and energy density compared to carbon-based active materials like graphite. However, they suffer from the disadvantage of exhibiting large volume changes during charge and discharge. This volume expansion and contraction of silicon-based active materials disrupts conductive connections within the negative electrode, leading to increased resistance and reduced lifetime performance. Furthermore, the solid electrolyte interphase (SEI) film formed during the lithium-ion battery formation process can rupture due to these volume changes in the silicon-based active material. This promotes side reactions in the electrolyte, causing increased resistance due to the increased thickness of the SEI film and electrolyte depletion, ultimately potentially degrading lifetime performance and storage characteristics.
[0035] To address the aforementioned issues, methods for combining carbon-based active materials have been studied. However, other problems exist, such as the formation of non-uniform films due to particle breakage caused by various factors, including the sphericity of the particles constituting the carbon-based active materials, the difference in mechanical strength between the carbon-based and silicon-based active materials, and the average particle size ratio and content ratio of silicon-based active materials to carbon-based active materials. Furthermore, the degradation of cycle life characteristics is caused by side reactions of the electrolyte.
[0036] The present invention addresses the aforementioned problem by designing the primary particles to have a sphericity within a specific range when the negative electrode active material comprises a silicon-based active material and a carbon-based active material comprising artificial graphite particles in the form of secondary particles formed by the aggregation of multiple primary particles.
[0037] Artificial graphite can be in the form of secondary particles formed by the aggregation of multiple primary particles.
[0038] The secondary particles refer to particles formed by the aggregation of multiple, for example, tens to hundreds, primary particles. When artificial graphite particles are in the form of secondary particles, voids can be formed within the artificial graphite particles. These voids can be empty spaces formed between primary particles, can be amorphous, and can exist in more than two forms.
[0039] Carbon-based active materials containing artificial graphite particles in the form of secondary particles have the following advantages: since lithium ions can move smoothly through the gaps formed between the secondary particles, the electrochemical reaction of lithium ions is promoted and the current conductivity is improved, thus increasing the charge and discharge speed.
[0040] The primary particles constituting the artificial graphite particles in the secondary particle form can have a sphericity of 0.60 to 0.78. When using a negative electrode active material comprising a silicon-based active material and a carbon-based active material comprising artificial graphite particles in the secondary particle form formed by the aggregation of multiple primary particles, it is preferable that, provided the primary particles meet the above-mentioned range, the carbon-based active material is less prone to breakage during the calendering process in the negative electrode preparation process, ensuring lithium-ion migration paths within the secondary particles, and maintaining the conductive network with the silicon-based active material.
[0041] Specifically, when the sphericity of the primary particles is less than 0.60, during the additional rolling process due to the low tap density and tortuosity, the carbon coating on the surface of the artificial graphite in the form of secondary particles may crack due to the relatively high particle strength of silicon, thus potentially increasing the Brunol-Emmett-Taylor (BET) specific surface area. If the BET specific surface area increases, the film may over-form on the electrode surface due to increased side reactions between the electrolyte and the cracked areas of the artificial graphite carbon coating. This can reduce the porosity at the upper end of the electrode, making it difficult for lithium ions to migrate to the lower end and leading to a problem of charge / discharge concentration on the silicon material located at the upper end of the electrode. Consequently, the expansion and contraction of the silicon-based active material present at the upper end of the electrode may be enhanced. If this process is repeated, additional side reactions may occur because the silicon-based active material at the upper end of the electrode can directly contact the electrolyte. Therefore, a portion of the surface of the silicon-based active material may become electrochemically inert, and the irreversible fixation of lithium ions on the surface of the silicon-based active material may lead to a decrease in battery capacity due to electrolyte decomposition and reduction of active silicon material, as well as a decrease in cycle life and an increase in battery resistance due to accelerated degradation of the upper end of the electrode caused by the degradation of the silicon-based active material at the upper end of the electrode.
[0042] In contrast, when the sphericity of primary particles is greater than 0.78, there is less breakage caused by silicon-based active material particles during the rolling process. However, due to the high sphericity, the exposure of graphite edge faces may increase. The edge faces of graphite correspond to the ends of the graphite crystal structure and have a greater number of active bonds than the internal basal faces. Since lithium-ion intercalation in graphite occurs through the edge faces rather than the basal faces, a higher edge / basal face ratio provides a morphology favorable for fast charging. However, if the edge / basal face ratio becomes excessively high due to the high sphericity of primary particles, graphite may react not only readily with lithium ions but also readily with the electrolyte solvent or lithium salts. Specifically, side reactions with the electrolyte may occur at the edge faces of graphite during charging, causing electrochemical decomposition of the electrolyte. The film formed by electrochemical decomposition is thick and unstable, potentially leading to decreased battery performance and shortened lifespan.
[0043] Furthermore, tortuosity may increase when the sphericity of primary particles is greater than 0.78. Tortuosity is an indicator of the degree of tortuosity of the path that lithium ions must traverse when passing through an electrode. For example, a lower tortuosity value means there are fewer factors hindering lithium ion transport. If the sphericity of the particles is high, the diffusion path of lithium ions becomes longer because the contact area between primary particles increases and the spacing between primary particles within secondary particles is relatively reduced. As a result, due to the increased overall tortuosity of the electrode, a structure is formed in which lithium ions have difficulty diffusing to the lower end of the electrode. If the lithium ion diffusion path is obstructed, the increased side reactions caused by accelerated degradation at the upper end of the electrode may lead to a decrease in battery capacity and an increase in resistance.
[0044] In this invention, the sphericity of the primary particles can be 0.60 or higher, 0.62 or higher, 0.64 or higher, or 0.66 or higher. The sphericity of the primary particles can be 0.78 or lower, 0.76 or lower, 0.74 or lower, or 0.72 or lower.
[0045] More specifically, the sphericity of primary particles can be in the range of 0.60 to 0.78, specifically 0.62 to 0.76, more specifically 0.64 to 0.74, or even more specifically 0.66 to 0.72. When the sphericity of primary particles meets the above range, side reactions with the electrolyte are reduced, which can prevent the reduction of discharge capacity, while achieving the effect of reducing battery resistance, and can simultaneously improve cycle life and fast charging performance.
[0046] The sphericity can be measured using an optical microscope (Keyence VHX-7000) in reflective mode with ring illumination for image analysis. Specifically, 4 mg of primary particles are dispersed in 2 ml of N-methyl-2-pyrrolidone (NMP) and then sonicated for 1 minute. Afterward, the solution is dropped onto a glass slide and covered with a coverslip to prepare a sample. The sample is placed on the stage of the optical microscope, and the microscope is focused at 300x magnification, at which point images of approximately 100 to 200 particles in the corresponding area can be obtained. Furthermore, the sphericity of each particle can be calculated using the automatic area measurement function in the corresponding device's software, and the sphericity of the primary particles can be quantified by averaging the calculated values. The sphericity of each particle is calculated using Equation 1 below.
[0047] [Formula 1]
[0048] Sphericity = 4πA / P 2
[0049] (P: Perimeter of the particle boundary, A: Area of the particle)
[0050] The improved lifespan characteristics and reduced battery resistance achieved by designing the sphericity of primary particles to meet the aforementioned range may not occur when using carbon-based active materials alone. In other words, the effects of this invention, achieved by controlling the sphericity value of primary particles, become apparent when the negative electrode active material comprises both carbon-based and silicon-based active materials.
[0051] In this invention, the average particle size (D) of the silicon-based active material 50 The average particle size (D) of artificial graphite particles in the form of secondary particles 50 The ratio of the two particles is in the range of 0.4 to 1. When using a negative electrode active material that contains silicon-based active material and artificial graphite particles in the form of secondary particles formed by the aggregation of multiple primary particles, the average particle size (D) of the silicon-based active material is within the range of 0.4 to 1. 50 The average particle size (D) of artificial graphite particles in the form of secondary particles 50 When the ratio of ) satisfies the above range, both the capacity characteristics and lifespan characteristics of the finally prepared lithium secondary battery can be ensured, so it is preferred.
[0052] Specifically, in the average particle size (D) of silicon-based active materials 50 The average particle size (D) of artificial graphite particles in the form of secondary particles 50 When the ratio of the silicon-based active material to the average particle size (D) is less than 0.4, the amount of lithium used as a component of the SEI film formed on the surface of the silicon-based active material increases due to the increased specific surface area of the silicon-based active material. Furthermore, due to the volume expansion of the silicon-based active material during battery operation, the SEI film formed on its surface is easily damaged, and the byproducts of the damaged SEI film may reduce the electrolyte impregnation capacity of the negative electrode by blocking its pores. As a result, the battery's capacity performance and fast-charging performance may decrease. Conversely, when the average particle size (D) of the silicon-based active material is less than 0.4, the amount of lithium used as a component of the SEI film formed on the surface of the silicon-based active material increases. 50 The average particle size (D) of artificial graphite particles in the form of secondary particles 50When the ratio of lithium ions to carbon-based active materials is greater than 1, the large difference in the degree of volume expansion between the interior and surface portions of the silicon-based active material particles may lead to accelerated degradation and particle breakage of the silicon-based active material. Specifically, when silicon-based and carbon-based active materials are used in combination, the lithium ion insertion potential of the silicon-based active material is higher than that of the carbon-based active material, thus the reaction of lithium ions inserting into the surface portion of the silicon-based active material particles preferentially occurs. However, since the energy required for lithium ions to diffuse into the interior of the silicon-based active material particles increases with the average particle size of the silicon-based active material, the reaction of lithium ions inserting into the carbon-based active material occurs preferentially over the reaction of lithium ions diffusing into the interior of the silicon-based active material particles. In other words, a situation occurs where lithium ions do not insert into the interior of the silicon-based active material particles. As described above, if the lithium ion insertion / extraction reaction occurs only at the surface portion of the silicon-based active material particles, particle breakage occurs due to the accelerated degradation rate of the silicon-based active material.
[0053] The average particle size (D) of silicon-based active materials 50 The average particle size (D) of artificial graphite particles in the form of secondary particles 50 The ratio can specifically range from 0.40 to 0.95, more specifically from 0.45 to 0.90, or even more specifically from 0.5 to 0.8. This applies to silicon-based active materials with an average particle size (D...). 50 The average particle size (D) of artificial graphite particles in the form of secondary particles 50 When the ratio of lithium to silicon meets the above range, the battery's capacity and lifespan performance are excellent because the problems of irreversible loss of available lithium and particle breakage of silicon-based active materials can be suppressed.
[0054] Furthermore, the ratio of the average particle size of the silicon-based active material to the average particle size of the primary particles in the secondary particle form of artificial graphite can be in the range of 0.65 to 1.15, specifically 0.70 to 1.10, more specifically 0.75 to 1.10, or even more specifically 0.80 to 1.05. When the above range is met, by preventing an excessive increase in the migration path of lithium ions within the primary particles relative to the silicon-based active material, the difference in degradation rate between the carbon-based and silicon-based active materials can be minimized, thus improving lifetime performance.
[0055] In this invention, the average particle size (D) of the primary particles 50The tap density can be in the range of 1 μm to 30 μm, specifically 3 μm to 25 μm, more specifically 5 μm to 18 μm, and even more specifically 7 μm to 13 μm. When the above ranges are met, the tap density is excellent because the density of primary particles in the secondary particle form of artificial graphite particles is not too low. With excellent tap density, the degree of thickness change during the rolling process to achieve the desired electrode thickness is small, thus suppressing particle breakage.
[0056] Secondary particle form of artificial graphite can be prepared by mixing primary particle form of artificial graphite particles with a binder material (e.g., pitch), spheroidizing, and heat-treating to aggregate the primary particle form of artificial graphite particles into secondary particles. Alternatively, when the artificial graphite particles are in secondary particle form, the artificial graphite particles can be prepared by mixing a carbon precursor and a binder material, performing spheroidizing and granulation processes to prepare a secondary particle form intermediate, and graphitizing the intermediate by heat-treating at a temperature above 3,000°C. In this case, the carbon precursor can be coal-based heavy oil, petroleum-based heavy oil, tar, pitch, or coke, and specifically at least one selected from the group consisting of needle coke, embedded coke, and coal tar pitch.
[0057] The carbon-based active material may further include an amorphous carbon coating disposed on the surface of the artificial graphite particles in the secondary particle form. The amorphous carbon coating helps improve the structural stability of the artificial graphite particles and prevents side reactions between the negative electrode active material and the electrolyte.
[0058] Based on the total weight of the carbon-based active material, the amorphous carbon coating can be formed in an amount of 0.1% to 10% by weight, preferably 1% to 5% by weight. The presence of the amorphous carbon coating can improve the structural stability of the carbon-based active material. However, since there is concern that excessive formation of the amorphous carbon coating may lead to an increase in specific surface area during the rolling of the negative electrode, resulting in a decrease in initial efficiency and deterioration of high-temperature storage performance, it is desirable to form the carbon coating within the above-mentioned amount range.
[0059] The amorphous carbon coating can be formed by heat treatment after providing a carbon coating precursor to artificial graphite particles.
[0060] The carbon coating precursor may comprise at least one selected from polymer resins and bitumen. Specifically, the polymer resin may comprise at least one selected from the group consisting of sucrose, phenolic resin, naphthalene resin, polyvinyl alcohol resin, furfuryl alcohol resin, polyacrylonitrile resin, polyamide resin, furan resin, cellulose resin, styrene resin, polyimide resin, epoxy resin, vinyl chloride resin, and polyvinyl chloride. The bitumen may comprise at least one selected from the group consisting of coal-based bitumen, petroleum-based bitumen, and mesophase bitumen. For promoting the uniform formation of the amorphous carbon coating, the heat treatment process for forming the amorphous carbon coating may be performed at a temperature of 1,000°C to 1,500°C.
[0061] In this invention, the average particle size (D) of the artificial graphite particles in the secondary particle form is... 50 It can be in the range of 5μm to 60μm, specifically 6μm to 35μm, more specifically 8μm to 20μm, or even more specifically 9μm to 14μm.
[0062] In this invention, the sphericity of the artificial graphite particles in the form of secondary particles can be in the range of 0.30 to 0.95, specifically 0.5 to 0.9, more specifically 0.60 to 0.85, or even more specifically 0.65 to 0.85.
[0063] In this invention, the BET specific surface area of the carbon-based active material can be as low as 0.05 m². 2 / g to 100m 2 / g, specifically 0.2m 2 / g to 10m 2 / g, more specifically 0.5m 2 / g to 1.5m 2 Within the range of / g. When the BET specific surface area of the carbon-based active material meets the above range, side reactions and uneven reactions with the electrolyte on the negative electrode surface can be prevented.
[0064] BET specific surface area can be measured using a BEL Sorption instrument (BEL Japan).
[0065] In this invention, the tap density of the carbon-based active material can be in the range of 0.3 g / cc to 2.0 g / cc, specifically 0.7 g / cc to 1.3 g / cc, and more specifically 0.95 g / cc to 1.10 g / cc. When the tap density of the carbon-based active material of this invention meets the above range, the solid content of the slurry increases due to the reduction of the space between particles during the granulation of secondary particles, thus providing advantages in the processability of mixed coating, and is therefore preferred.
[0066] In the present invention, the silicon-based active material may include a silicon-based negative electrode active material, for example, silicon (Si), a Si-Me alloy (where Me is at least one selected from the group consisting of aluminum (Al), tin (Sn), magnesium (Mg), copper (Cu), iron (Fe), lead (Pb), zinc (Zn), manganese (Mn), chromium (Cr), titanium (Ti) and nickel (Ni)), silicon oxide (SiO x , 0<x<2) and a silicon-carbon composite (Si / C composite), most preferably, may include at least one selected from the group consisting of silicon (Si), silicon oxide (SiO x , 0<x<2) and a silicon-carbon composite (Si / C composite).
[0067] In the present invention, the average particle diameter (D 50 ) of the silicon-based active material may be in the range of 0.5 μm to 60 μm, specifically 1 μm to 35 μm, more specifically 3 μm to 20 μm, even more specifically 5 μm to 10 μm, and still more specifically 7 μm to 9 μm.
[0068] In the present invention, the content ratio of the carbon-based active material to the silicon-based active material may be a weight ratio of 50:50 to 99:1, specifically 70:30 to 97:3, more specifically 80:20 to 97:3, and even more specifically 85:15 to 97:3. When the weight ratio satisfies the above range, side reactions caused by volume expansion of the silicon-based active material can be effectively minimized, while the capacity of the lithium secondary battery is improved.
[0069] The content of the negative electrode active material in the negative electrode active material layer may be 60 wt% to 99 wt%, preferably 75 wt% to 98 wt%. In the case where the amount of the negative electrode active material is within the above range, the desired capacity of the battery can be achieved.
[0070] On the basis of containing the above negative electrode active material, the negative electrode active material layer may further include a binder, a conductive agent and / or a thickener.
[0071] The binder is a component that facilitates bonding between the active material and / or the current collector, wherein the binder may generally be included in the negative electrode active material layer in an amount of 0.1 wt% to 30 wt%, preferably 1 wt% to 10 wt%.
[0072] The binder may include at least one selected from the group consisting of: polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber and fluororubber, preferably at least one selected from polyvinylidene fluoride and styrene-butadiene rubber.
[0073] Any thickener used in conventional lithium secondary batteries can be used as a thickener, and an example of this is carboxymethyl cellulose (CMC).
[0074] The conductive agent is a component used to further improve the conductivity of the negative electrode active material, wherein the conductive agent may be included in the negative electrode active material layer in an amount of 0.1% to 30% by weight, preferably 1% to 10% by weight.
[0075] Any negative electrode conductive agent can be used without particular restrictions, as long as it is conductive and does not cause chemical changes in the battery. For example, conductive materials such as: graphite (e.g., natural or synthetic graphite); carbon black (e.g., acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermally cracked carbon black); conductive fibers (e.g., carbon fibers or metal fibers); metal powders (e.g., fluorocarbon powder, aluminum powder, and nickel powder); conductive whiskers (e.g., zinc oxide whiskers and potassium titanate whiskers); conductive metal oxides (e.g., titanium oxide); or polyphenylene derivatives. Specific examples of commercial conductive agents include acetylene black-based products (Chevron Chemical, Denka (Singapore Pte Ltd), or Gulf Oil), Ketjen black, ethylene carbonate (EC)-based products (Armak), Vulcan XC-72 (Cabot), and Super P (Timcal Graphite & Carbon).
[0076] The thickness of the negative electrode active material layer can be in the range of 10 μm to 300 μm, specifically 50 μm to 200 μm, but is not limited thereto.
[0077] The negative electrode active material layer can be prepared by applying a negative electrode slurry, which is made by adding the negative electrode active material and optionally a binder, thickener and / or conductive agent to a solvent, to a negative electrode current collector and then calendering and drying the coated negative electrode current collector. In this case, the solvent may contain water or an organic solvent, such as NMP (N-methyl-2-pyrrolidone), and more specifically water.
[0078] The negative electrode can be prepared by mixing the negative electrode active material with an optional binder and conductive agent in a solvent (e.g., NMP (N-methyl-2-pyrrolidone) or water) to prepare a negative electrode slurry, then coating the negative electrode current collector with the negative electrode slurry and drying and calendering the coated negative electrode current collector.
[0079] Since the negative electrode according to the present invention comprises the negative electrode active material, wherein the loss of carbon-based active material is prevented and the mobility of lithium ions is ensured by controlling the sphericity of the primary particles constituting the carbon-based active material and the amount of silicon-based active material, it has superior capacity characteristics, fast charging performance and cycle life characteristics compared with conventional negative electrodes, and the rate of increase in battery resistance is controlled.
[0080] The BET specific surface area of the negative electrode can be as small as 0.1 m². 2 / g to 30m 2 / g, specifically 0.5m 2 / g to 10m 2 / g, more specifically 1m 2 / g to 6m 2 / g, or even more specifically 2m 2 / g to 4m 2 / g, and more specifically 2.1m 2 / g to 3.0m 2 Within the range of / g. When the BET specific surface area of the negative electrode meets the above range, the breakage of artificial graphite particles in the form of secondary particles can be prevented, and the mobility of lithium ions can be maximized, which is therefore preferred.
[0081] The porosity of the negative electrode can be in the range of 15% to 40%, specifically 25% to 35%.
[0082] The porosity of the negative electrode can be calculated using Equation 2 below.
[0083] [Equation 2]
[0084] Porosity (%) = {1 - (electrode density of negative electrode / true density of negative electrode)} × 100
[0085] In Equation 2, the true density of the negative electrode is calculated using the true density of the negative electrode active material, conductive agent and binder contained in the negative electrode active material layer, based on the mixing ratio in the negative electrode active material layer, and the electrode density of the negative electrode is the density of the negative electrode active material layer measured by sampling the negative electrode at a predetermined size.
[0086] The true density of the negative electrode active material, conductive agent, and binder is measured using a gas hydrometer (Quantachone).
[0087] Lithium secondary batteries
[0088] Next, the lithium secondary battery according to the present invention will be described.
[0089] The lithium secondary battery according to the present invention comprises a negative electrode, a positive electrode and an electrolyte, and may further comprise a separator as needed. In this case, since the negative electrode is the same as the negative electrode according to the present invention described above, a detailed description thereof will be omitted, and the remaining components other than the negative electrode will be described below.
[0090] positive electrode
[0091] The positive electrode according to the present invention comprises a positive electrode material mixture layer containing a positive electrode active material, a positive electrode conductive agent and a positive electrode binder. The positive electrode can be prepared by a method in which a positive electrode slurry containing a positive electrode active material, a positive electrode binder, a positive electrode conductive agent and a solvent is applied onto a positive electrode current collector, followed by rolling to form a positive electrode material mixture layer.
[0092] The positive electrode current collector is not particularly limited as long as it has electrical conductivity without causing chemical changes in the battery, and for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver and the like can be used.
[0093] The positive electrode active material is a compound capable of reversibly intercalating and deintercalating lithium, and the positive electrode active material may specifically include a lithium metal oxide containing lithium and at least one metal such as cobalt, manganese, nickel or aluminum. More specifically, the lithium metal oxide may include lithium manganese-based oxides (e.g., LiMnO2, LiMn2O4, etc.), lithium cobalt-based oxides (e.g., LiCoO2, etc.), lithium nickel-based oxides (e.g., LiNiO2, etc.), lithium nickel manganese-based oxides (e.g., LiNi 1-Y Mn Y O2 (where 0<Y<1), LiMn 2-Z Ni z O4 (where 0<Z<2, etc.), lithium nickel cobalt-based oxides (e.g., LiNi 1-Y1 Co Y1 O2 (where 0<Y1<1, etc.), lithium manganese cobalt-based oxides (e.g., LiCo 1-Y2 Mn Y2 O2 (where 0<Y2<1), LiMn 2-Z1 Co z1 O4 (where 0<Z1<2, etc.), lithium nickel manganese cobalt-based oxides (e.g., Li(Ni p Co q Mn r )O2 (where 0<p<1, 0<q<1, 0<r<1 and p+q+r=1) or Li(Ni p1 Co q1 Mn r1)O4 (where 0<p1<2, 0<q1<2, 0<r1<2 and p1+q1+r1=2), etc.), or lithium nickel cobalt transition metal (M) oxides (for example, Li(Ni p2 Co q2 Mn r2 M S2 )O2 (where M is selected from the group consisting of aluminum (Al), iron (Fe), vanadium (V), chromium (Cr), titanium (Ti), tantalum (Ta), magnesium (Mg) and molybdenum (Mo), and p2, q2, r2 and s2 are the atomic fractions of the respective independent elements, where 0<p2<1, 0<q2<1, 0<r2<1, 0<s2<1 and p2+q2+r2+s2=1), etc., and any one thereof or a mixture of two or more thereof may be included.
[0094] Specifically, the positive electrode active material may include a lithium transition metal oxide represented by the following [Formula 1].
[0095] [Formula 1]
[0096] Li x Ni a Co b M 1 c M 2 d O2
[0097] In Formula 1, M 1 is at least one selected from Mn and Al, and in terms of durability, Mn or a combination of Mn and Al may be preferred.
[0098] M 2 may be at least one selected from the group consisting of zirconium (Zr), yttrium (Y), boron (B), tungsten (W), magnesium (Mg), cerium (Ce), hafnium (Hf), tantalum (Ta), lanthanum (La), titanium (Ti), strontium (Sr), barium (Ba), fluorine (F), phosphorus (P) and sulfur (S).
[0099] x represents the atomic fraction of lithium in the lithium transition metal oxide, where x may satisfy 0.90≤x≤1.1, preferably satisfy 0.95≤x≤1.08, and more preferably satisfy 1.0≤x≤1.08.
[0100] a represents the atomic fraction of nickel among the metal elements other than lithium in the lithium transition metal oxide, where a may satisfy 0.50≤a<1.0, 0.60≤a≤0.95, 0.65≤a≤0.95, or 0.80≤a≤0.95. In the case where the amount of nickel satisfies the above range, high capacity characteristics can be achieved.
[0101] b represents the atomic fraction of cobalt among the metal elements other than lithium in the lithium transition metal oxide, wherein b can satisfy 0<b<0.5, 0<b<0.4, or 0.01≤b≤0.3.
[0102] c represents the atomic fraction of M among the metal elements other than lithium in the lithium transition metal oxide 1 , wherein c can satisfy 0<c<0.5, 0<c<0.4, or 0.01≤c≤0.3.
[0103] d represents the atomic fraction of M among the metal elements other than lithium in the lithium transition metal oxide 2 , wherein d can satisfy 0≤d≤0.1 or 0≤d≤0.05.
[0104] Based on the total weight of the positive electrode material mixture layer, the content of the positive electrode active material may be 60 wt% to 99 wt%, preferably 70 wt% to 99 wt%, more preferably 80 wt% to 98 wt%.
[0105] The positive electrode binder is a component that facilitates the binding between the positive electrode active material and the positive electrode conductive agent and the binding to the current collector.
[0106] Examples of the positive electrode binder may be polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene (PE), polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, or various copolymers.
[0107] Based on the total weight of the positive electrode material mixture layer, the content of the positive electrode binder may generally be 1 wt% to 20 wt%, preferably 1 wt% to 15 wt%, more preferably 1 wt% to 10 wt%.
[0108] The positive electrode conductive agent is a component used to further improve the conductivity of the positive electrode active material, and is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, conductive materials may be used, such as: carbon powder, for example, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, or thermal black; graphite powder, for example, natural graphite, artificial graphite, or graphite with a well-developed crystal structure; conductive fibers, for example, carbon fibers or metal fibers; fluorocarbon powder; conductive powder, for example, aluminum powder and nickel powder; conductive whiskers, for example, zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, for example, titanium oxide; or polyphenylene derivatives.
[0109] Based on the total weight of the positive electrode material mixture layer, the content of the positive electrode conductive agent may generally be 1 wt% to 20 wt%, preferably 1 wt% to 15 wt%, more preferably 1 wt% to 10 wt%.
[0110] The solvent for the positive electrode slurry may include organic solvents such as dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), and acetone, and may be used in a certain amount to achieve the desired viscosity when the positive electrode active material, positive electrode binder, and positive electrode conductive agent are included. For example, the solvent content may be such that the concentration of the solid components comprising the positive electrode active material and optionally the positive electrode binder and positive electrode conductive agent is in the range of 50% to 95% by weight, preferably 70% to 95% by weight, and more preferably 70% to 90% by weight.
[0111] electrolytes
[0112] As the electrolyte used in this invention, various electrolytes suitable for lithium secondary batteries can be used, such as organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, or molten inorganic electrolytes, and their types are not particularly limited.
[0113] Specifically, the electrolyte may contain an organic solvent and a lithium salt.
[0114] Any organic solvent can be used without particular limitation, as long as it serves as a medium through which ions involved in the electrochemical reactions of the battery can move. Specifically, as organic solvents, ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone can be used; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; or carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (PC); alcohol solvents such as ethanol and isopropanol; nitriles such as R-CN (where R is a straight-chain, branched, or cyclic C2-C20 hydrocarbon group and may contain a double-bonded aromatic ring or ether bond); amides such as dimethylformamide; dioxolane such as 1,3-dioxolane; or sulfolane. Among these solvents, carbonate solvents are preferred. For example, a mixture of cyclic carbonates (e.g., ethylene carbonate or propylene carbonate) with high ionic conductivity and high dielectric constant that can improve the charge and discharge performance of the battery and low viscosity linear carbonate compounds (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred.
[0115] The lithium salt can be used without particular restrictions, as long as it is a compound capable of providing lithium ions for use in lithium secondary batteries. Specifically, as lithium salts, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, LiB(C2O4)2, or combinations thereof can be used. The lithium salt can be used in a concentration range of 0.1 M to 5.0 M, preferably 0.1 M to 3.0 M. Since the electrolyte can have suitable conductivity and viscosity when the concentration of the lithium salt is within the above range, excellent electrolyte performance can be obtained, and lithium ions can move efficiently.
[0116] To improve battery life characteristics, suppress battery capacity reduction, and increase battery discharge capacity, in addition to the components mentioned above, the electrolyte may also contain additives. For example, the electrolyte may contain at least one additive selected from the group consisting of: cyclic carbonate compounds, halogen-substituted carbonate compounds, sulcolone compounds, sulfate / ester compounds, phosphate / ester compounds, borate / ester compounds, nitrile compounds, benzene compounds, amine compounds, silane compounds, and lithium salt compounds.
[0117] Examples of the cyclic carbonate compounds may include vinylene carbonate (VC) or vinylene carbonate.
[0118] Examples of the halogen-substituted carbonate compounds may include fluoroethylene carbonate (FEC).
[0119] Examples of the sulfonyl compounds may include at least one compound selected from the group consisting of 1,3-propanesulfonyl lactone (PS), 1,4-butanesulfonyl lactone, ethanesulfonyl lactone, 1,3-propenesulfonyl lactone (PRS), 1,4-butenesulfonyl lactone and 1-methyl-1,3-propenesulfonyl lactone.
[0120] Examples of the sulfate / ester compounds may include ethylene sulfate (Esa), trimethylene sulfate (TMS), or methyltrimethylene sulfate (MTMS).
[0121] Examples of the phosphate / ester compounds may include at least one compound selected from the group consisting of: lithium difluoro(bis(oxalato)phosphate), lithium difluorophosphate, tetramethyltrimethylsilyl phosphate, trimethylsilyl phosphite, tri(2,2,2-trifluoroethyl) phosphate, and tri(trifluoroethyl) phosphite.
[0122] Examples of the borate / ester compounds may be tetraphenylborate, lithium difluoroborate oxalate (LiODFB), and lithium bis(oxalate)borate (LiB(C2O4)2, LiBOB).
[0123] Examples of the nitrile compounds may include at least one compound selected from the group consisting of succinic anionibacterium, adiponitrile, acetonitrile, propionitrile, butyronitrile, valerate, octanoic anionibacterium, heptanoic anionibacterium, cyclopentaneformitrile, cyclohexaneformitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, phenylacetonitrile, 2-fluorophenylacetonitrile, and 4-fluorophenylacetonitrile.
[0124] Examples of the benzene compounds may include fluorobenzene, examples of the amine compounds may include triethanolamine or ethylenediamine, and examples of the silane compounds may include tetravinylsilane.
[0125] The lithium salt compound is a compound that is different from lithium salts contained in non-aqueous electrolytes, and the lithium salt compound may include lithium difluorophosphate (LiDFP), LiPO2F2 or LiBF4.
[0126] Based on the total weight of the electrolyte, the content of the additive can be from 0.1% to 10% by weight, preferably from 0.1% to 5% by weight.
[0127] diaphragm
[0128] The separator separates the negative and positive electrodes and provides a path for lithium ions to move. Any separator can be used without particular limitation, as long as it is typically used in lithium-ion secondary batteries. Specifically, porous polymer membranes can be used as separators, such as porous polymer membranes prepared from polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers, or laminates of two or more layers thereof. Additionally, typical porous nonwoven fabrics can be used, such as nonwoven fabrics formed from high-melting-point glass fibers or polyethylene terephthalate fibers. Furthermore, coated separators containing ceramic components or polymer materials can be used to ensure heat resistance or mechanical strength.
[0129] The lithium secondary battery according to the present invention, as described above, can be used to manufacture battery packs. The battery pack includes components in which the lithium secondary battery according to the present invention is electrically connected and a battery pack housing housing the components. The battery pack housing may include busbars, cooling units, external terminals, etc., for electrically connecting the lithium secondary battery. The battery pack can be installed in a vehicle. The vehicle may be, for example, an electric vehicle, a hybrid vehicle, or a plug-in hybrid vehicle. The vehicle includes four-wheeled vehicles or two-wheeled vehicles. In particular, because the lithium secondary battery according to the present invention has high energy density and excellent fast-charging performance, it can be usefully used as a battery for electric vehicles.
[0130] Methods of implementing the invention
[0131] The present invention will be described in detail below with reference to specific embodiments. However, the following embodiments are provided merely to provide a clearer and more detailed understanding of the invention, and are not intended to limit the scope of the invention.
[0132] Examples and Comparative Examples
[0133] Example 1
[0134] A negative electrode slurry was prepared by adding a negative electrode active material, a conductive agent (carbon black), and a binder (SBR-CMC) to distilled water in a weight ratio of 95.6:1.0:3.4.
[0135] The negative electrode active material is a mixture of carbon-based and silicon-based active materials in a weight ratio of 90:10. The carbon-based active material consists of artificial graphite particles in the form of secondary particles formed by the aggregation of multiple primary particles, with an amorphous carbon coating formed on its surface. The primary particles have an average particle size (D) of 9 μm. 50 The sphericity is 0.75. Furthermore, the carbon coating content is 2.5% by weight based on the carbon-based active material. Additionally, the average particle size (D) of the artificial graphite particles is... 50 Its thickness is 12 μm, its sphericity is 0.82, and its specific surface area is 0.8 m². 2 / g. Furthermore, the silicon-based active material is Si / C and has an average particle size of 8 μm (D 50 ).
[0136] The negative electrode was prepared by applying a negative electrode slurry onto a copper current collector, followed by drying, calendering, and vacuum drying to form a negative electrode active material layer (thickness: 70 μm). The porosity of the negative electrode was 28%.
[0137] Example 2
[0138] The negative electrode was prepared in the same manner as in Example 1, except that artificial graphite particles in the form of secondary particles formed by the aggregation of multiple primary particles were used as the carbon-based active material, wherein the primary particles have an average particle size of 7.9 μm (D). 50 The artificial graphite particles have a sphericity of 0.65 and an average particle size of 10.5 μm (D). 50 ), sphericity of 0.76 and 0.9m 2 Specific surface area per g. The porosity of the negative electrode is 28%.
[0139] Comparative Example 1
[0140] The negative electrode was prepared in the same manner as in Example 1, except that artificial graphite particles in the form of secondary particles formed by the aggregation of multiple primary particles were used as the carbon-based active material, wherein the primary particles have an average particle size of 5 μm (D). 50 The artificial graphite particles have a sphericity of 0.57 and an average particle size of 7.2 μm (D). 50 ), sphericity of 0.63 and 0.4m 2 Specific surface area per g. The porosity of the negative electrode is 28%.
[0141] Comparative Example 2
[0142] The negative electrode was prepared in the same manner as in Example 1, except that artificial graphite particles in the form of secondary particles formed by the aggregation of multiple primary particles were used as the carbon-based active material, wherein the primary particles have an average particle size of 13.3 μm (D). 50 The artificial graphite particles have a sphericity of 0.91 and an average particle size of 16.5 μm (D). 50 ), sphericity of 0.89 and 1.3m 2 Specific surface area per g. The porosity of the negative electrode is 28%.
[0143] Comparative Example 3
[0144] The negative electrode was prepared in the same manner as in Comparative Example 1, except that an average particle size (D) was used. 50 A 6μm Si / C matrix was used as the silicon-based active material. The porosity of the negative electrode was 28%.
[0145] Comparative Example 4
[0146] The negative electrode was prepared in the same manner as in Example 1, except that an average particle size (D) was used. 50 A 14 μm Si / C matrix was used as the silicon-based active material. The porosity of the negative electrode was 28%.
[0147] Comparative Example 5
[0148] The negative electrode was prepared in the same manner as in Example 1, except that an average particle size (D) was used. 50 A 3μm Si / C matrix was used as the silicon-based active material. The porosity of the negative electrode was 28%.
[0149] [Table 1]
[0150] 1) Sphericity
[0151] Sphericity was measured using an optical microscope (Keyence VHX-7000) in reflection mode with annular illumination for image analysis. Specifically, 4 mg of particles contained in each negative electrode active material used in Examples 1 and 2 and Comparative Examples 1 to 5 were dispersed in 2 ml of N-methyl-2-pyrrolidone (NMP) and then sonicated for 1 minute. The solution was then dropped onto a glass slide and covered with a coverslip to prepare a sample. The sample was then placed on the stage of the optical microscope, and the focus was adjusted to a magnification of 300x, at which point images of approximately 100 to 200 particles in the corresponding region were obtained. The sphericity of each particle was calculated using the automatic area measurement function in the optical microscope software, and the corresponding values were averaged and shown in Table 1 above.
[0152] [Formula 1]
[0153] Sphericity = 4πA / P 2
[0154] (P: Perimeter of the particle boundary, A: Area of the particle)
[0155] 2) Tap density
[0156] 40g of the negative electrode active material powder contained in Examples 1 and 2 and Comparative Examples 1 to 5 were placed in a container and tapped 1000 times to compact the powder. The volume and mass were then measured to calculate the tap density. The tap densities calculated from the artificial graphite particles of Examples 1 and 2 and Comparative Examples 1 to 5 are shown in Table 1 above.
[0157] 3) BET specific surface area of the negative electrode
[0158] The specific surface area of the negative electrodes of Examples 1 and 2 and Comparative Examples 1 to 5 was measured as follows, using 6 300 rolled electrodes were punched using a diameter electrode punching machine, and the punched electrodes were placed in a BET sample cell and then measured using a BEL Sorption instrument (BEL Japan). The measurement results of the carbon-based active materials of Examples 1 and 2 and Comparative Examples 1 to 5, and the negative electrodes of Examples 1 and 2 and Comparative Examples 1 to 5 are shown in Table 1 above.
[0159] 4) Evaluation of tortuosity
[0160] Using the negative electrodes of Examples 1 and 2 and Comparative Examples 1 to 5, electrode assemblies were prepared by placing a separator between the two negative electrodes. The electrode assemblies were placed in a battery case, and an electrolyte containing 1M lithium salt (LiPF6) was injected (ethylene carbonate (EC): ethyl methyl carbonate (EMC) = 3:7 v / v%), and the battery was aged for 12 to 24 hours to prepare a symmetrical coin cell (symmetrical cell). Then, after applying a current with a frequency of 0.1 Hz to 1,000,000 Hz and an amplitude of 10 Mv to the prepared symmetrical coin cell, the electrode pore resistance was measured using a graph measured by electrochemical impedance spectroscopy (EIS) to calculate the average migration distance (Ls) of lithium ions within the negative electrode active material layer, and the tortuosity (Ls / L0) was calculated by dividing Ls by the thickness (L0) of the negative electrode active material layer.
[0161] The tortuosity calculated using this method is shown in Table 1 above.
[0162] Experimental Example
[0163] Experimental Example 1: Evaluation of Initial Efficiency and Discharge Capacity
[0164] (Preparation of a coin half-cell)
[0165] Electrode assemblies were prepared by providing a separator between the negative electrode and the lithium counter electrode in Examples 1 and 2 and Comparative Examples 1 to 5, and an electrolyte was injected after the electrode assemblies were placed in a battery case to prepare a coin half-cell.
[0166] (Evaluation of initial efficiency and discharge capacity)
[0167] The coin half-cells according to Examples 1 and 2 and Comparative Examples 1 to 5 were each charged at room temperature (25°C) in constant current-constant voltage (CCCV) mode to 0.1 C to 0.005 V, with a cutoff condition of 0.005 C, and discharged in CC mode at 0.1 C to 1.5 V to measure the discharge capacity and initial efficiency.
[0168] The measurement results are shown in Table 2 below.
[0169] Experimental Example 2: Capacity Retention Evaluation
[0170] A coin half-cell was prepared in the same manner as in Experimental Example 1. Furthermore, with the above charge-discharge cycle defined as one cycle, 300 cycles were performed at 25°C. Subsequently, based on the discharge capacity after the first cycle (set to 100%), the discharge capacity (capacity retention) after 300 cycles was measured, and the results are shown in Table 2 below.
[0171] [Table 2]
[0172] Referring to Table 2, it can be understood that the coin half-cells of Examples 1 and 2 (where the negative electrode active materials used satisfy the sphericity range of primary particles according to the invention, comprising carbon-based and silicon-based active materials, and the ratio of the average particle size of the silicon-based active materials to the average particle size of the artificial graphite particles in the form of secondary particles satisfies the range of the invention) have better discharge capacity, initial efficiency, and capacity retention after 300 cycles than the coin half-cells of Comparative Examples 1 to 3, which are outside the sphericity range of primary particles according to the invention.
[0173] Furthermore, it can be understood that the coin half-cells according to Examples 1 and 2 have better discharge capacity, initial efficiency, and capacity retention after 300 cycles than the coin half-cells of Comparative Examples 4 and 5, which satisfy the range of sphericity of primary particles according to the invention but deviate from the ratio of the average particle size of the silicon-based active material to the average particle size of the artificial graphite particles in the form of secondary particles according to the invention.
[0174] Reference Example
[0175] Reference Example 1
[0176] The negative electrode was prepared in the same manner as in Example 1, except that the negative electrode active material consisted only of carbon-based active material and was not mixed with silicon-based active material.
[0177] See Example 2
[0178] The negative electrode was prepared in the same manner as in Example 2, except that the negative electrode active material consisted only of carbon-based active material and was not mixed with silicon-based active material.
[0179] See Example 3
[0180] The negative electrode was prepared in the same manner as in Comparative Example 1, except that the negative electrode active material consisted only of carbon-based active material and was not mixed with silicon-based active material.
[0181] See Example 4
[0182] The negative electrode was prepared in the same manner as in Comparative Example 2, except that the negative electrode active material consisted only of carbon-based active material and was not mixed with silicon-based active material.
[0183] Refer to Experiment Example 1: Evaluation of Initial Efficiency and Discharge Capacity
[0184] (Preparation of a coin half-cell)
[0185] Electrode assemblies were prepared by setting a separator between each of the negative electrodes prepared in Reference Examples 1 to 4 and the lithium counter electrode, and after placing the electrode assemblies in a battery case, an electrolyte was injected to prepare a coin half-cell.
[0186] (Evaluation of initial efficiency and discharge capacity)
[0187] The coin half-cells according to Reference Examples 1 to 4 were each charged at room temperature (25°C) in CCCV mode at 0.1 C to 0.005 V with a cutoff condition of 0.005 C, and discharged in CC mode at 0.1 C to 1.5 V to measure the discharge capacity and initial efficiency.
[0188] The measurement results are shown in Table 3 below.
[0189] Refer to Experiment Example 2: Evaluation of Capacity Retention
[0190] A coin half-cell was prepared in the same manner as in Reference Experimental Example 1. Furthermore, when the above charge-discharge cycle was defined as one cycle, 300 cycles were performed at 25°C. Subsequently, based on the discharge capacity after the first cycle (set to 100%), the discharge capacity (capacity retention) after 300 cycles was measured, and the results are shown in Table 3 below.
[0191] [Table 3]
[0192] Referring to Table 3, it can be confirmed that at least one of the discharge capacity, initial efficiency, and capacity retention rate after 300 cycles of Reference Example 1 is not superior to Reference Examples 2 to 4, which are outside the sphericity range of the present invention.
[0193] This indicates that even when using a carbon-based active material containing artificial graphite particles in the form of secondary particles, which aggregate multiple primary particles within the sphericity range of the present invention, as the negative electrode active material, no effect of improving initial efficiency and cycle life characteristics is obtained when the carbon-based active material is not mixed with a silicon-based active material.
[0194] Therefore, it can be clearly understood that the sphericity of the primary particles according to the present invention within a certain range can only exhibit significant effects when the negative electrode active material contains not only carbon-based active materials but also silicon-based active materials.
Claims
1. A negative electrode comprising: Current collector; and A negative electrode active material layer is disposed on at least one surface of the current collector. The negative electrode active material layer comprises carbon-based active materials and silicon-based active materials. The carbon-based active material comprises artificial graphite particles in the form of secondary particles formed by the aggregation of multiple primary particles. The primary particles have a sphericity of 0.60 to 0.78, and The average particle size (D) of the silicon-based active material 50 The average particle size (D) of the artificial graphite particles in the secondary particle form 50 The ratio is 0.4 to 1.
2. The negative electrode according to claim 1, wherein the primary particles have an average particle size (D) of 1 μm to 30 μm. 50 ).
3. The negative electrode according to claim 1, wherein the average particle size (D) of the artificial graphite particles in the form of secondary particles is... 50 The range is from 5μm to 60μm.
4. The negative electrode according to claim 1, wherein the artificial graphite particles in the form of secondary particles have a sphericity of 0.30 to 0.
95.
5. The negative electrode according to claim 1, wherein the carbon-based active material has a density of 0.05 μm. 2 / g to 100m 2 Brunol-Emmett-Taylor (BET) specific surface area per g.
6. The negative electrode according to claim 1, wherein the carbon-based active material has a tap density of 0.3 g / cc to 2.0 g / cc.
7. The negative electrode according to claim 1, wherein the average particle size of the silicon-based active material is in the range of 0.5 μm to 60 μm.
8. The negative electrode according to claim 1, wherein the silicon-based active material comprises at least one selected from the group consisting of silicon (Si), silicon oxide (SiO x , 0<x<2), and a silicon-carbon composite.
9. The negative electrode according to claim 1, wherein the weight ratio of the carbon-based active material to the silicon-based active material is in the range of 50:50 to 99:
1.
10. The negative electrode according to claim 1, wherein the negative electrode has a 0.1m... 2 / g to 30m 2 / g BET specific surface area.
11. A lithium secondary battery, comprising: The negative electrode according to claim 1; The positive electrode facing the negative electrode; A diaphragm disposed between the negative electrode and the positive electrode; and Non-aqueous electrolyte.
